2015
DOI: 10.1364/ol.40.005283
|View full text |Cite
|
Sign up to set email alerts
|

Single-frequency fiber laser at 1950  nm based on thulium-doped silica fiber

Abstract: A single-frequency fiber laser operating at 1950 nm has been demonstrated in an all-fiber distributed Bragg reflection laser cavity by using a 1.9 cm commercially available thulium-doped silica fiber, for the first time, to the best of our knowledge. The laser was pumped by a 793 nm single-mode diode laser and had a threshold pump power of 75 mW. The maximum output power of the single longitudinal mode laser was 18 mW and the slope efficiency with respect to the launched pump power was 11%. Moreover, the linew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…The maximum slope efficiency is 12.8%, with Tm 3+ doping concentration of 15% (The maximum slope efficiency diagram is shown in Figure ). The slope efficiency of Tm:YAS fiber lasers were comparable to some latest reported Tm 3+ ‐doped glass fiber lasers . Two reasons may contributed to this result: (i) The homemade Tm:YAS optical fiber are suffering from a relatively high attenuation originated from the purity of raw material, and the operation process for fiber drawing also needs to be further optimized.…”
Section: Resultssupporting
confidence: 59%
“…The maximum slope efficiency is 12.8%, with Tm 3+ doping concentration of 15% (The maximum slope efficiency diagram is shown in Figure ). The slope efficiency of Tm:YAS fiber lasers were comparable to some latest reported Tm 3+ ‐doped glass fiber lasers . Two reasons may contributed to this result: (i) The homemade Tm:YAS optical fiber are suffering from a relatively high attenuation originated from the purity of raw material, and the operation process for fiber drawing also needs to be further optimized.…”
Section: Resultssupporting
confidence: 59%
“…Meanwhile, the ultra-high single-transverse-mode power and brightness obtained by Design B offer promising prospects in pumping fiber amplifiers and solid-state laser systems. In addition, the reduced lateral beam divergence observed for Design B allows the lateral bulk-coupling or the use of relatively simple and low-cost optics for coupling into commercial single-mode fibers, such as SM1950 or PM1950 [ 10 , 27 ], and photonic integrated circuit (PIC) applications [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…After decades of research, SFFLs have found a variety of uses in optical sensing, optical measurement, and coherent optical communication. [1][2][3][4][5] The most commonly used configurations for SFFLs include the construction of distributed feedback (DFB) fiber lasers, [6][7][8] distributed Bragg reflector (DBR) fiber lasers, [9][10][11][12][13][14] and ring-cavity fiber lasers with ultranarrow-bandwidth filters. [15][16][17] However, the DBR and DFB fiber lasers cannot efficiently absorb the pump power and also need accurate and costly fiber Bragg gratings (FBGs), whilst the ring-cavity fiber lasers have a complex and unstable structure.…”
Section: Introductionmentioning
confidence: 99%